2006
DOI: 10.1111/j.1539-6924.2006.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Agro‐Biodiversity, Uncertainty, and Perceived Control: A Comparative Risk Perception Study in Austria and China

Abstract: The biogeographical centers of origin of important food crops-called Vavilov centers-are considered to be crucial sources of genetic diversity for present and future crop-breeding programs and thus for human food safety worldwide. Global environmental change and more intensified modes of crop production may cause genetic erosion (loss of traditional crop varieties and loss of crop wild relatives), especially in Vavilov centers. The present study focused on how the risk of genetic erosion (or loss of agro-biodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…Earlier research, with Western populations, indicates that perceptions of hazard tend to decrease with increased perceived control and familiarity and increase with increased likelihood of injury and severity of injury (e.g., Wogalter et al, 1999). However, other research suggests that Chinese perceptions of control may differ from those of more western populations (e.g., Schmidt and Wei, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier research, with Western populations, indicates that perceptions of hazard tend to decrease with increased perceived control and familiarity and increase with increased likelihood of injury and severity of injury (e.g., Wogalter et al, 1999). However, other research suggests that Chinese perceptions of control may differ from those of more western populations (e.g., Schmidt and Wei, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…For example, Slovic et al (1979) found that, for technologies (i.e., nuclear power) and activities (i.e., recreational activities), likelihood of injury is the strongest predictor. Schmidt and Wei (2006) used a psychometric approach in their study of risk perceptions in Austria and China. They obtained evidence for three main risk factors (catastrophic risk, uncertainty, and relevance) that were broadly consistent with those identified in earlier risk perception studies.…”
Section: Introductionmentioning
confidence: 99%
“…China, however, maintains also a high diversity in traditional crops and crop wild relatives and is confronted with the risk of genetic erosion (Gao 2003;Schmidt and Wei 2006). Given that China is aVected by ongoing socioeconomic and environmental changes (e.g.…”
Section: Geographic Focus: China and Southeast Asiamentioning
confidence: 99%
“…Une des explications proposées pour expliquer la perte de confiance des sociétés occidentales envers les gouvernements et les scientifiques qui les représentent est celle de la théorie de la modernité réfléchie (reflexive modernization) [20]. Les populations orientales tendraient à croire que l'être humain contrôle la nature, la société et la technologie et préfèreraient laisser l'analyse des risques potentiels aux experts.…”
Section: -La Perception Sociale De La Technologieunclassified